Relations between urban configuration, urban surfaces, and environmental noise in the Aburrá Valley (Colombia) (2023)
ABSTRACT : The increase in the levels of noise pollution in large cities depends on several factors that are not always linked to the noise source (road traffic, aircrafts traffic, rail traffic, industries, leisure activities, among others). There are other types of variables that greatly affect this type of contamination. This is the case of urban envelopes that, depending on their configuration and materiality, can have a great impact on the propagation of noise. This research work seeks to study different envelope conditions and urban configuration of facades in the Aburrá Valley Colombia and analyze the possible relationship with noise propagation. For this, the space-time dynamics of environmental noise are characterized based on information collected by seven monitoring stations distributed throughout this urban area. With these data, the main sources, and temporalities of noise in the the Aburrá Valley are identified. Subsequently, different compounds are studied that, given their characteristics, can absorb the noise produced in urban street canyons. For this, an impedance tube is built based on the ISO 10534-1 Standard and the sound absorption coefficient of various compounds and sound-absorbing materials is measured. Subsequently, urban configurations such as urban street canyons are studied where the arrangement of balconies and sound-absorbing material may have an impact on the propagation of noise. Finally, the implications of the results on urban noise mitigation strategies in the Aburrá Valley are discussed. For this, a 1:10 scale model of an average urban street canyon is built in the Aburrá Valley and equivalent continuous level measurements are made by analyzing different configurations on the facade in terms of sound-absorbing materials and balcony configuration to find the insertion loss. The results of this study provide evidence that porous ceramic materials such as refractory brick, porous minerals such as pumice stone and natural fibers such as cork or rice husks can mitigate environmental noise. In addition, it was possible to appreciate that the urban configurations of facades in which there are balconies cause an increase in the levels of environmental noise, due to the arrangement of the balconies on the pedestrian’s platforms, present in the Aburrá Valley, which tend to generate a conservation field for acoustic energy produced by noise sources.